Three-dimensional morphological condylar and mandibular changes in a patient with juvenile idiopathic arthritis: interdisciplinary treatment - G. Farronato; C. Bellintani; U. Garagiola; P. Cressoni; P. Sarzi Puttini; F. Atzeni; M. Cazzola (PAGEPress Publications, 2014)
Temporomandibular joint (TMJ) involvement is common but usually delayed in patients with juvenile idiopathic arthritis (JIA). We describe the case of a JIA patient with bilateral TMJ involvement, mandibular retrognathia, bone erosion, and severely restricted mouth opening. The use of cone beam computed tomography and a 3D diagnostic protocol in young patients with JIA provides reliable, accurate and precise quantitative data and images of the condylar structures and their dimensional relationships. Analgesics and conventional disease modifying antirheumatic drugs were ineffective, but interdisciplinary treatment with etanercept and a Herbst functional appliance improved functional TMJ movement and bone resorption.